Inventory control for the closed-loop supply chain with technological progress and planned shortages. (14th January 2022) - Chen, Shih-Pin; Lin, Yu-Min
The impact of Industry 4.0 has received much attention in academic and practice fields. Therefore, understanding the effects of technological progress in production on closed-loop supply chain (CLSC) inventory management is critical. In view of profit efficiency, this paper investigates the effects of technological progress in production on inventory policies in a CLSC considering planned shortages. A CLSC production-inventory model is proposed to jointly determine sale and collection prices and production time points. The representative numerical results show that technological progress in manufacturing inconsistently has a positive impact on the NPU because the total quantity produced and cycle length vary. The impact of technological progress may be greater in the manufacturing process than in the remanufacturing process. The results can aid production managers in finding optimal production-inventory strategies considering technological progress and planned shortages. Additionally, the results provide useful information regarding the impact of technological progress in selecting investment targets. [Received: 5 August 2020; Accepted: 16 March 2021]